Highlights of the Latest Developments in Radiopharmaceuticals for Infection Imaging and Future Perspectives - Dadachova, Ekaterina; Rangel, Drauzio E. N. (Frontiers in Medicine, 2022)
COVID-19 pandemic has heightened the interest toward diagnosis and treatment of infectious diseases. Nuclear medicine with its powerful scintigraphic, single photon emission computer tomography (SPECT) and positron emission tomography (PET) imaging modalities has always played an important role in diagnosis of infections and distinguishing them from the sterile inflammation. In addition to the clinically available radiopharmaceuticals there has been a decades-long effort to develop more specific imaging agents with some examples being radiolabeled antibiotics and antimicrobial peptides for bacterial imaging, radiolabeled anti-fungals for fungal infections imaging, radiolabeled pathogen-specific antibodies and molecular engineered constructs. In this opinion piece, we would like to discuss some examples of the work published in the last decade on developing nuclear imaging agents for bacterial, fungal, and viral infections in order to generate more interest among nuclear medicine community toward conducting clinical trials of these novel probes, as well as toward developing novel radiotracers for imaging infections.